Efficient, footprint-free human iPSC genome editing by consolidation of Cas9/CRISPR and piggyBac technologies - Wang, Gang (Nat Protoc, 2016)
Genome editing of human induced pluripotent stem cells (iPSCs) offers unprecedented opportunities for in vitro disease modeling and personalized cell replacement therapy. The introduction of Cas9-directed genome editing has expanded adoption of this approach. However, marker free genome editing using standard protocols remains inefficient, yielding desired targeted alleles at a rate of approximately 1–5%. We developed a protocol based on a doxycycline-inducible Cas9 transgene carried on a piggyBac transposon to enable robust and highly efficient Cas9-directed genome editing, so that a parental line can be expeditiously engineered to harbor many separate mutations. Treatment with doxycycline and transfection with gRNA, donor DNA, and piggyBac transposase resulted in efficient, targeted genome editing and concurrent scarless transgene excision. Using this approach, in seven weeks it is possible to efficiently obtain genome edited clones with minimal off-target mutagenesis and with indel mutation frequencies of 40–50% and homology-directed repair frequencies of 10–20%.